Getting the right traits: reproductive and dispersal characteristics predict the invasiveness of herbaceous plant species - Moravcová, Lenka; Pyšek, Petr; Jarošík, Vojtěch; Pergl, Jan (PLoS One, 2015)
To better understand the effect of species traits on plant invasion, we collected comparative data on 20 reproductive and dispersal traits of 93 herbaceous alien species in the Czech Republic, central Europe, introduced after 1500 A. D. We explain plant invasion success, expressed by two measures: invasiveness, i.e. whether the species is naturalized but non-invasive, or invasive; and dominance in plant communities expressed as the mean cover in vegetation plots. We also tested how important reproductive and dispersal traits are in models including other characteristics generally known to predict invasion outcome, such as plant height, life history and residence time. By using regression/classification trees we show that the biological traits affect invasion success at all life stages, from reproduction (seed production) to dispersal (propagule properties), and the ability to compete with resident species (height). By including species traits information not usually available in multispecies analyses, we provide evidence that traits do play important role in determining the outcome of invasion and can be used to distinguish between alien species that reach the final stage of the invasion process and dominate the local communities from those that do not. No effect of taxonomy ascertained in regression and classification trees indicates that the role of traits in invasiveness should be assessed primarily at the species level.
Keywords: fyziologie rostlin; rozmnožování; vývoj rostlin; Reproduction; zavlečené druhy; Plant Development; Introduced Species; Plant Physiological Phenomena